Geoffrey Clarke a sculptor's prints (Sansom & Company, 2012)
Geoffrey Clarke: a sculptor's prints -- Invisible worlds -- Sculptural visions -- Cultures of production / Geoffrey Clarke -- 'Exposition of a Belief' (1951) -- Catalogue